Convergence properties of generalized Lupaş-Kantorovich operators - M. Qasim; A. Khan; Z. Abbas; M. Mursaleen (Karpatsʹkì Matematičnì Publìkacìï, 2021)
In the present paper, we consider the Kantorovich modification of generalized Lupaş operators, whose construction depends on a continuously differentiable, increasing and unbounded function $ρ$. For these new operators we give weighted approximation, Voronovskaya type theorem, quantitative estimates for the local approximation.